Project weather - Steele, Philip (New York, Windmill Books, 2020)
BECOME AN EXPERT in what happens in the sky and all around the earth with this interactive book packed with super-cool facts and hands-on projects. Create your own mini water cycle, track a thunderstorm and make fog in a jar! Illustrated step-by-step projects encourage hands-on-learning and offer a unique approach to topics like rainbows and climate change. Get ready to see weather in a whole new way with lift-up flaps, amazing images and fun activities on every page!